PHARMACOCORRECTION WITH ANGIOLIN OF ENERGY METABOLISM DISORDERS DUE TO CHRONIC ALCOHOL INTOXICATION IN THE BRAIN OF RATS - Бєленічев І. Ф.; Павлюк І. В.; Кучеренко Л. І. (World of Medicine and Biology, 2016)
Experimental chronic alcohol intoxication was caused by 30-days intragastric administration of 15% ethanol (4 g/kg, 10 days), then by administration of 15% ethanol, 6 g/kg (10 days) and then by administration of 25% ethanol (4 g/kg, 10 days) in white outbred male rats weighing 160-180 g. Chronic alcohol intoxication results on the 15th day of alcohol withdrawal in a pronounced inhibition of oxidative energy production, activation of compensatory pathways of ATP formation - glycolysis and Roberts shunt, which, however, do not supply to the full extent the brain with energy and cause the development of lactate acidosis and the deficiency of the neurotransmitter amino acids - GABA and glutamate, as well as glycine. Correction with Angiolin at a dose of 100 mg / kg (SPC «Pharmatron», Ukraine) of oxidative metabolism violation by intragastrical administration for 14 days after alcogolization increases the activity of own bioenergetic processes due to the "adding" of additional shunts of brain energy metabolism and intensification of aerobic reactions of substrate oxidation and it limits activity of Roberts shunt and thereby "retains" the resources of GABA and glutamate. Reference drug Mildronate administration in the same way in dose of 250 mg/kg did not affect significantly on studied energy metabolism parameters of experimental animals’ brain. Received results experimentally ground the use of Angiolin in complex treatment of alcoholism with the aim of normalizing the energy metabolism of the brain.
Keywords: chronic alcohol intoxication; brain; energy metabolism; Angiolin; Mildronate